Simplify: `(-x^2*y^2)/(x^(1/2)*y^0)`

Expert Answers
justaguide eNotes educator| Certified Educator

The expression `(-x^2*y^2)/(x^(1/2)*y^0)` has to be simplified.

`(-x^2*y^2)/(x^(1/2)*y^0)`

= `(-x^2*y^2)/(x^(1/2)*1)`

= `-x^(2-1/2)*y^2`

= `-x^(3/2)*y^2`

The simplified form of `(-x^2*y^2)/(x^(1/2)*y^0) = -x^(3/2)*y^2`

oldnick | Student

`-(x^2y^2)/(x^(1/2)y^0)=` `-x^(2-1/2)y^(2-0)=-x^(3/2)y^2=-xy^2sqrt(x)`

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question